2015
DOI: 10.1371/journal.pone.0129584
|View full text |Cite
|
Sign up to set email alerts
|

Association between Aspirin Therapy and Clinical Outcomes in Patients with Non-Obstructive Coronary Artery Disease: A Cohort Study

Abstract: BackgroundPresence of non-obstructive coronary artery disease (CAD) is associated with increased prescription of cardiovascular preventive medications including aspirin. However, the association between aspirin therapy with all-cause mortality and coronary revascularization in this population has not been investigated.Methods and FindingsAmong the cohort of individuals who underwent coronary computed tomography angiography (CCTA) from 2007 to 2011, 8372 consecutive patients with non-obstructive CAD (1-49% sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…This is despite the available evidence suggesting that individuals with nonobstructive CAD have an increased risk for adverse clinical outcomes compared with patients with normal coronary arteries 4, 7, 8. Moreover, there is evidence that medical therapy (in particular, aspirin and statins) improves clinical outcomes in patients with nonobstructive CAD 17, 18. Consistent with this, we found important differences in clinical outcomes in patients receiving OMT, particularly being at lower risk for all‐cause hospitalization compared with those who were not receiving OMT.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the available evidence suggesting that individuals with nonobstructive CAD have an increased risk for adverse clinical outcomes compared with patients with normal coronary arteries 4, 7, 8. Moreover, there is evidence that medical therapy (in particular, aspirin and statins) improves clinical outcomes in patients with nonobstructive CAD 17, 18. Consistent with this, we found important differences in clinical outcomes in patients receiving OMT, particularly being at lower risk for all‐cause hospitalization compared with those who were not receiving OMT.…”
Section: Discussionmentioning
confidence: 99%
“…For symptomatic patients with suspected coronary artery disease, the presence and severity of coronary artery disease identified on CCTA is associated with the increased use of preventive therapies such as aspirin and statin therapies 13 , 14 as well as lifestyle modification 14 , 15 . A single-center registry of 8,372 patients with nonobstructive coronary artery disease identified by CCTA also showed that statin therapy was associated with lower mortality, but aspirin therapy was only associated with lower mortality in high-risk patients 16 , 17 . However, all of these observational studies have many potential biases, including case selection bias and confounding by treatment allocation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CCTA could result in increased use of medications and invasive procedures, because this test reveals the presence of coronary atherosclerosis even in the subclinical stage . Of note, the increased use of preventive medications in patients with nonobstructive CAD detected by CCTA leads to improvements in lipid profile and blood pressure control; and, moreover, it can reduce the risk of mortality and cardiovascular events . Therefore, the clinical outcomes following CCTA should be assessed on a long‐term basis, because the prognosis can be determined by the intensified preventive medications and the increased use of ICA and coronary revascularization following anatomical testing, as well as the potential missed diagnosis by functional testing.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Of note, the increased use of preventive medications in patients with nonobstructive CAD detected by CCTA leads to improvements in lipid profile and blood pressure control; and, moreover, it can reduce the risk of mortality and cardiovascular events. [29][30][31] Therefore, the clinical outcomes following CCTA should be assessed on a long-term basis, because the prognosis can be determined by the intensified preventive medications and the increased use of ICA and coronary revascu- the Better Evaluation of Acute Chest Pain with Computed Tomography Angiography (BEACON) trial with 1 month of follow-up, 4 and several cohort studies with 1 or 2 months of follow-up duration. [33][34][35] Considering the possible increase in the use of invasive procedures driven by CCTA results, as well as its potential benefit for prevention of future cardiovascular events, the impact of the initial diagnostic approach should be assessed on a long-term basis.…”
Section: Ccta Vs Usual Care: Comparison Of Longerterm Outcomesmentioning
confidence: 99%